Trypanosomiasis – In Cross Bred Jersey Cow And Its Therapeutic Management- A Report Of Two Cases - Sarkar , Pradip; Datta , Sanjib (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Pathogenic species of salivarian trypanosomes are present throughout the vast areas of Africa, Middle East Asia, South East Asia, Latin America and causes disease in cattle, sheep, goat, water buffalo, pigs, horses camels, wildlifes and also in human. Trypanosoma sp. is transmitted mechanically by interrupted biting of Tabanus fly. Occurrence of sub-clinical trypanosomiasis in cross bred jersey is not very common. Buffaloes may act as reservoir host of Trypanosoma evansi. Additional stress i.e. hard work, transportation, inclement weather and vaccination may be responsible for outbreak of trypanosomiasis (Soulsby, 1986) in farm animals.The present communication reports two cases of acute trypanosomiasis (Surra) in crossbred jersey cows.